Proprotein convertase subtilisin / kexin 9 (PCSK9) inhibitors and the future of dyslipidemia therapy: an updated patent review (2011-2015). (1st December 2016) - Elbitar, Sandy; Khoury, Petra El; Ghaleb, Youmna; Rabès, Jean-Pierre; Varret, Mathilde; Seidah, Nabil G.; Boileau, Catherine; Abifadel, Marianne
ABSTRACT: Introduction: The identification by Abifadel et al. in 2003 of the first mutations of PCSK9 was the major breakthrough in the cholesterol field that led to a new therapeutic target. This discovery paved the way to new lipid lowering drugs reducing LDL-cholesterol levels through the inhibition of PCSK9. Two anti-PCSK9 monoclonal antibodies have received FDA and EMA approvals: Alirocumab and Evolocumab. Areas covered: This article reviews the different strategies that are pursued to modulate the functional activity of PCSK9 for lowering LDL-cholesterol levels. It also provides a brief overview of the patents related to PCSK9 from 2011 until the end of 2015. This review is addressed to researchers from academia and pharmaceutical companies who are engaged in PCSK9 research/cholesterol regulation. Readers will gain an up-to-date overview of the different strategies that have been investigated to reduce PCSK9, focusing on anti-PCSK9 monoclonal antibodies and the related clinical trials. Expert opinion: Anti-PCSK9 antibodies are a new class of lipid lowering drugs with promising results in reducing LDL-cholesterol. Long-term ongoing studies investigating on a large scale the efficacy and safety of the anti-PCSK9 antibodies and their cardiovascular outcomes are eagerly awaited.